INTERNATIONAL PRACTICES OF IMPLEMENTATION OF INNOVATIONS IN AGRICULTURE - Razakova Barno Sayfievna; Bilaldinova Iparhon Farhod qizi (Scholar Express Journal, 2023)
The most serious problem today is the rapid population growth rate on our planet, which makes it more difficult for farmers and other agricultural producers to provide food for the population. Innovation plays a key role in stimulating this process in the agricultural sector. The authors in their article consider innovation processes in agriculture and world experience of their implementation.
Keywords: Agriculture; innovative development; strategy